The Munich-Evaluation-of-Mentoring-Questionnaire (MEMeQ) – a novel instrument for evaluating protégés' satisfaction with mentoring relationships in medical education. Issue 1 (December 2015) - Schäfer, Matthias; Pander, Tanja; Pinilla, Severin; Fischer, Martin; von der Borch, Philip; Dimitriadis, Konstantinos
Abstract Background Despite the widespread recognition of the importance of mentoring in medical education, valid and reliable instruments for evaluating the relationship of mentors and protégés are lacking. The aim of this study was to develop a feasible instrument to measure the satisfaction with mentoring relationships. Methods Based on two existing questionnaires, the authors developed an instrument to evaluate the weighted satisfaction of mentoring relationships, emphasizing the protégés' individual expectations and needs. Protégés first define individual areas of interest in their mentoring relationship, then assign relative levels of personal importance to them and finally rate their individual level of satisfaction with their mentors' support in each area of interest. In order to evaluate psychometric properties as well as acceptance and feasibility the investigators conducted a multi-method-study. Results 134 protégés were included in the study. The instrument was neither perceived as distressing nor time-consuming. The two scores of the questionnaire correlated closely with the overall satisfaction regarding mentoring relationships (OSM, Rho: 0.66, p <.001 and Rho: 0.53, p < .001). Conclusions The authors propose MEMeQ as a reliable, valid and flexible instrument for measuring the weighted satisfaction of protégés with their individual mentoring relationship in medical education. Further research is needed to evaluate the generalizability of MEMeQ across other institutions and mentoring programs to add to its validity.